Seropositivity rates of zoonotic pathogens in small ruminants and associated public health risks at informal urban markets in Zambia - Lysholm, S.; Fischer, K.; Lindahl, Johanna F.; Munyeme, M.; Wensman, Jonas Johansson (Elsevier, 2022)
Informal livestock markets are an important source of animal-derived proteins for growing urban populations in countries such as Zambia. In parallel, they can also constitute pathways of zoonotic pathogen transmission to humans. This risk is aggravated by limited disease monitoring and poor control systems with regards to biosecurity and public health. The aim of this study was to investigate the risks for spread of zoonotic diseases in Zambia's two largest informal small ruminant markets, located in Lusaka and Kasumbalesa, through combining seroepidemiology with interviews and observations. In April, May and September 2018, serum samples (n = 237) were collected and analysed for antibodies for the zoonotic pathogens Brucella spp., Coxiella (C.) burnetii and Rift Valley fever virus (RVFV), using commercially available enzyme linked immunosorbent assays (ELISA). In addition, slaughterhouse activities were observed and semi-structured interviews and focus group discussions held with slaughterhouse workers and small ruminant traders, focusing on the handling of animals and meat, and the perceptions of zoonotic disease risks at slaughter and consumption. The study found seropositivity rates of 10.1% (95% confidence interval [CI] 6.60–14.7) for Brucella spp., 5.9% (95% CI 3.27–9.71) for C. burnetii, and 0.8% (95% CI 0.10–3.01) for RVFV. Interviews with value chain members and observations at the slaughterhouse revealed unsanitary procedures and multiple occupational hazards for slaughterhouse workers. This study showed that the Zambian informal small ruminant trade system poses risks to public health, and that these risks are exacerbated by a lack of information about food-borne diseases and how associated risks can be mitigated amongst value chain actors. The results of this study can be used to formulate preventive measures to improve informal meat markets and reduce the risks to public health.